Implementation of Adiwiyata Program in the Effort to Create Environmental Cultured School in Banda Aceh: Implementation of - Desfandi, Mirza; Maryani, Enok; Disman, Disman (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
This research examined the implementation of Adiwiyata Program in the effort to create environmental cultured school in Banda Aceh. This research used quantitative study paradigm by using survey technique. This study was conducted in ten schools in Banda Aceh from elementary to secondary school levels by involving 452 respondents, which consist of school principals/vice principals, Adiwiyata coordinators, administrative staff and students. Data collection was done through questionnaire and observation. The result of study showed that in general Adiwiyata Program implementation is in effective category. This described that in general the four components of Adiwiyata Program had been implemented effective. Nevertheless, result of study found various obstacles encountered by school in implementing Adiwiyata Program. This article delve and describe in depth the implementation of Adiwiyata Program, so various obstacles encountered by school can be found out in order to implement Adiwiyata Program in Banda Aceh. It is hoped that the result of study can give insight to stakeholder to take the steps forward in the effort to create environmental cultured school. Keywords: Implementation, Adiwiyata Program, Environmental cultured school